Vliv developerských rezidenčních projektů na tržní hodnotu stavebních pozemků - Vaněčka, Jan (Vysoké učení technické v Brně. Ústav soudního inženýrství, 2025)
Diplomová práce se zaměřuje na analýzu vlivu jednotlivých etap výstavby rezidenčních developerských projektů na tržní hodnotu stavebních pozemků. Prostřednictvím případových studií tří lokalit je zkoumán vývoj realizovaných a inzerovaných cen v různých fázích výstavby a identifikovány faktory, které tento vývoj ovlivňují. Práce dokládá, že jednotlivé etapy výstavby mají rozdílný dopad na cenovou hladinu, a to nejen v rámci samotného projektu, ale i v jeho širším okolí. Výsledky ukazují, že pro správnou interpretaci cenových údajů je nezbytná kvalitativní analýza doprovodných investic a tržního kontextu.

The thesis focuses on the analysis of the impact of individual stages of construction of residential development projects on the market value of building land. Through case studies of three sites, the evolution of realised and advertised prices at different stages of construction is examined and the factors influencing this evolution are identified. The thesis demonstrates that different stages of construction have different impacts on price levels, not only within the project itself but also in its wider surroundings. The results show that a qualitative analysis of the accompanying investments and the market context is necessary for a correct interpretation of the price data.
The impact of residential development projects on the market value of building plots
Keywords: Diplomová práce; tržní hodnota; stavební pozemky; developerské projekty; fáze výstavby; realizované ceny; inzerované ceny; katastr nemovitostí; analýza; Diploma thesis; market value; building land; development projects; construction phase; realised prices; advertised prices; land register; analysis